Mediation in Islamic family law disputes: an overview & experience of the UKM Legal Aid and Mediation Centre - Asma Hakimah Ab Halim,; Siti Naaishah Hambali,; Fatimah Yusro Hashim,; Nazura Abdul Manap, (Fakulti Undang-undang, Universiti Kebangsaan Malaysia, 2020)
Legal Aid and Mediation Clinic, UKM (now known as KBGM) first started mediation services in Islamic family law disputes in June 2015. The need for such initiatives is clearly driven by KBGM's past experience in dealing with various cases involving family disputes Islam. This study aims to identify the Mediation method as a potential solution medium to be adapted as a dispute resolution medium for conflicts involving the family. The method of this study is qualitative with reference to relevant writing sources on mediation, observation and analysis of cases that have been conducted in KBGM. Mediation as an alternative dispute resolution is an option that can be implemented given the cost effectiveness, fast procedures and there is an element of confidentiality. This method makes it easier for those who are not able to get access to justice. The KGBM experience shows that a large number of Islamic family law disputes can be resolved through mediation rather than a court process. The settlement through this mediation can also preserve family ties as the parties themselves will choose and reach an agreement towards resolving their dispute harmoniously. This is important because if a case is brought to court, usually the parties will continue to dispute because the process in court is 'adversarial' compared to the alternative solution through mediation. Disputes related to divorce, hadhanah, inheritance and common property are some of the cases that can be mediated. During the engagement, KGBM also found some aspects that need to be improved and improved to ensure that this method can continue to be preserved. Therefore, this writing is a sharing of KGBM experience in mediation and further suggests some improvements to improve this mediation service.